Crystallographic investigation into the self-assembly, guest binding, and flexibility of urea functionalised metal-organic frameworks. Issue 9 (2nd September 2018) - Marshall, Ross J.; McGuire, Jake; Wilson, Claire; Forgan, Ross S.
Abstract: Introduction of hydrogen bond functionality into metal-organic frameworks can enhance guest binding and activation, but a combination of linker flexibility and interligand hydrogen bonding often results in the generation of unwanted structures where the functionality is masked. Herein, we describe the self-assembly of three materials, where Cd 2+, Ca 2+, and Zn 2+ are linked by N, N ʹ-bis(4-carboxyphenyl)urea, and examine the effect of the urea units on structure formation, the generation of unusual secondary building units, structural flexibility, and guest binding. The flexibility of the Zn MOF is probed through single-crystal to single-crystal transformations upon exchange of DMF guests for CS2, showing that the lability of the [Zn4 O(RCO2 )6 ] cluster towards solvation enables the urea linkers to adopt distorted conformations as the MOF breathes, even facilitating rotation from the trans/trans to the trans/cis conformation without compromising the overall topology. The results have significant implications in the mechanistic understanding of the hydrolytic stability of MOFs, and in preparing heterogeneous organocatalysts. Abstract :